2020
DOI: 10.1186/s12916-020-01764-x
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides for the detection of diastolic dysfunction and heart failure with preserved ejection fraction—a systematic review and meta-analysis

Abstract: Background An overview of the diagnostic performance of natriuretic peptides (NPs) for the detection of diastolic dysfunction (DD) and heart failure with preserved ejection fraction (HFpEF), in a non-acute setting, is currently lacking. Methods We performed a systematic literature search in PubMed and Embase.com (May 13, 2019). Studies were included when they (1) reported diagnostic performance measures, (2) are for the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 79 publications
(147 reference statements)
3
21
0
2
Order By: Relevance
“… 23 , 24 , 25 In a recent systematic review, the low sensitivity of NT‐proBNP was again confirmed. 26 Nevertheless, some clinicians still use the low NT‐proBNP as an absolute rule‐out method.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 , 25 In a recent systematic review, the low sensitivity of NT‐proBNP was again confirmed. 26 Nevertheless, some clinicians still use the low NT‐proBNP as an absolute rule‐out method.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography was performed on anesthetized rats with no stress testing incorporated. Cardiac blood panels did not include any markers for inflammation or brain type natriuretic peptide (BNP), although new studies are suggesting that BNP should not be considered a gold standard marker for diagnosing HFpEF ( 31 , 32 ). The number of animals for histological analysis could be higher; however, with ANOVA analysis, reporting of significance is conservative, and one can be confident of any metric reported to be different.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 51 studies found that NPs have reasonable diagnostic performance in the detection of HFpEF in a nonacute setting (area under the receiver operating characteristics curve 0.80; 95% CI [0.73-0.87]; I 2 =86%) and are also a useful tool for ruling out diastolic dysfunction. 7 Interestingly, lower levels of NT-proBNP are found in patients with HFpEF in comparison with those with HF with reduced ejection fraction (HFrEF), 8,9 possibly because of the association of NPs with end-diastolic wall stress that appears to be lower in HFpEF. 10 Obokata et al attributed the lower NPs in HFpEF to lower wall stress due to pericardial restraint, which might be a dominant mechanism in some HfpEF patients.…”
Section: Myocardial Stretch and Injury Natriuretic Peptidesmentioning
confidence: 99%